Computer usage and access in low-income urban communities. - Araque, J.C.; Maiden, R.P.; Bravo, N.; Estrada, I.; Evans, R.; Hubchik, K.; Kirby, K.; Reddy, M. (Computers in Human Behavior, 2013)
Abstract: The purpose of this study is to examine the effects of home computer access on low-income families participating in the Computer for Families program. The study focused on participants (1) general computer usage, access and knowledge; (2) employment; (3) education; and (4) their children’s-computer access, usage and academic performance. The study methodology consisted of a quasi-experimental design using qualitative and quantitative approaches, including focus groups, pretests and post-tests, and self-reported surveys with experimental and control groups. Statistically significant findings suggest that participants in the Computers for Families program were more likely than non-participants to have access to the Internet from home, use a computer for more than 1h per day, complete online job applications, and submit job applications and resumes electronically. Social and behavioral implications regarding computer access and usage in low-income urban communities are discussed.